The Impact of Using Gamification on English language learning in increasing Learning Motivation - Kharizmi, Muhammad; Pratiwi Handayani, Tri; Amaliyah Mushthoza, Dina; Rohmiyati, Yuli; Binusa Suryadi, Satrio (International Journal of Language and Ubiquitous Learning, 2024)
Background. 21st century education demands changes in learning methods to increase students’ learning motivation. Gamification, or the use of game elements in a learning context, has been recognized as an effective tool to increase student engagement and motivation. However, more in-depth research is still needed to evaluate the effectiveness of gamification in increasing the motivation to learn English among English Language Education students. Purpose. The main purpose of this research is to evaluate the effectiveness of using gamification in increasing the motivation of students in learning English. Method. Through a quantitative approach and survey method, this research aims to investigate the experience, perception, and level of student learning motivation related to the use of gamification in English language learning. English Education. The survey was conducted by distributing questionnaires compiled based on related literature and previous research on gamification. The survey steps are voluntary and the confidentiality of the data is strictly maintained. Results. Based on the results of the analysis of the sixth questionnaire, gamification proved to have a positive impact on increasing students’ learning motivation in learning English. The majority of respondents feel effective or enthusiastic about the use of gamification. However, there are a small number of respondents who feel neutral towards the concept of gamification. Further evaluation and efforts to expand the understanding and application of gamification need to be done. Conclusion. This research shows that the use of gamification in English language learning promises to increase students’ learning motivation. However, continuous evaluation and improvement is required to maximize its potential use. Thus, gamification can be considered as an effective learning strategy in the context of learning English in the 21st century education era.